IMPLIKASI DISPENSASI PERKAWINAN TERHADAP EKSISTENSI RUMAH TANGGA DI PENGADILAN AGAMA SEMARANG - HM Mawardi Muzzamil; Muhammad Muhammad Kunardi (UNISSULA, 2014)
One of the requirements is the age of marriage the bride, the groom reaches the age of 19 years and the woman has reached the age of 16 years. The age limit is to maintain the health of spouses and offspring. If the prospective bride marriage age limit is not sufficient, it must be granted a dispensation from religious court. This marriage dispensation will bring legal consequences for the parties and the implications of the existence of households bride, considering marriage performed by the bride who has not been physically and psychologically mature. The approach used in this study is a socio-juridical. Specifications of this research is descriptive analysis. The results of this study indicate that the arguments raised in the petition in the Religious marriage dispensation Semarang are fears of acts prohibited by religion and the future wife was pregnant. Basic considerations judge in giving marriage dispensation in the Religious Semarang is the provision of Article 7 paragraph (2) of Law No. 1 of 1974. The implications of marriage dispensation in Semarang religious court of the existence of the household is underage marriage causes of conflict in the household lead to divorce, other than that the cause of death in babies born to mothers or because of the lack of physical maturity of the female.